PELATIHAN DASAR-DASAR AKUNTANSI DAN PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN UMKM MENGGUNAKAN APLIKASI AKUNTANSI BERBASIS CLOUD SI APIK - Novitasari Novitasari; Ridwan Zulfi Agha; Nedsal Sixpria; Atyanto Mahatmyo; Hastuti Redyanita (Universitas Mataram, 2023)
New entrepreneurs in Bogor Regency have difficulty measuring their financial performance accurately. This is because novice entrepreneurs still have minimal knowledge of accounting, ignore the importance of recording financial transactions so they do not have proper financial reports according to accounting standards. The solution to this problem is to hold an accounting literacy training program and mentoring for budding entrepreneurs. The aim of this activity is to increase the knowledge of novice entrepreneurs regarding the basics of accounting and provide assistance to novice entrepreneurs in preparing their financial reports using the SI Apik cloud-based accounting application. Training was carried out at the Bogor Regency Cooperatives and UMKM Service. Starting with giving a pretest to the participants to find out the initial knowledge of accounting that the training participants have, continued with providing basic accounting material and a workshop on preparing financial reports using the SI APIK application, then ending with completing the posttest by the participants. From the pretest results, the percentage of participants who understood the basics of accounting was only 43.70%, after attending the training it increased to 97.41%, or there was an increase in knowledge of the basics of accounting among training participants by 53.71%. Meanwhile, in terms of skills in preparing financial reports using the SI APIK application, before the training was given, only 3.33% of participants knew and understood the SI APIK application, however after being given the training this increased to 90%, or there was an increase in participants' understanding and skills in making bookkeeping and preparing financial reports with SI APIK of 86.67%. Accounting training activities are able to increase participants' basic knowledge of accounting and improve participants' skills in using the SI APIK cloud-based accounting application.